Impactos econômicos das energias renováveis na economia nordestina - Barbosa, Wladimir de Macedo (2024)
Energy is essential for human development, with the possibility of depletion of conventional energy matrices and serious environmental imbalance, society's awareness is growing in the search for renewable sources of clean and sustainable energy production, given that in addition to causing substantially lower environmental impacts, they also avoid the emission of tons of carbon dioxide into the atmosphere. Among the main types of renewable energies we can mention solar energy, wind energy, hydraulic energy, biomass, biogas, biodiesel and geothermal, where these energies are increasingly gaining ground and competing with the energies already existing in Brazil, with a great pace of growth in the Northeast region, given the strong natural potential of winds and the high incidence of solar radiation. This dissertation analyzed the economic impacts generated by public investments in renewable energy in the Northeast region carried out by the Financing Program for Distributed Micro and Minigeneration of Electric Energy and Offgrid Systems (FNE Sol) maintained by Banco do Nordeste do Brasil (BNB), using the Input-Output Matrix methodology. The results show a considerable evolution in the economic activity of energy production in the Northeast. Due to the strong growth in the production of wind and solar renewable energy, with economic impacts quantified in Gross Value Added (GVA), Employment, Wage Mass and Taxes.